2022
DOI: 10.2147/ppa.s364520
|View full text |Cite
|
Sign up to set email alerts
|

Consensus on the Objectives of an Educational Intervention for Patients with Oropharyngeal Dysphagia and Their Informal Caregivers: A Delphi Study

Abstract: Purpose In the absence of literature allowing for an evidence-based approach to therapeutic patient education (TPE) in Oropharyngeal Dysphagia (OD), this study aims to reach a consensus of experts on the content of a competency framework of an educational program for OD patients and their informal caregivers (ICGs). Methods We used the Delphi consensus-building method. Four categories of experts were recruited: 12 patients, 17 ICGs, 46 healthcare professionals (HCP) (ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…This could assist in overcoming challenges associated with meal preparation and selection, given many carers have reported to resorting to trial-and-error methods (Howells et al, 2021a;Nund et al, 2014aNund et al, , 2014c. Knowing how to select and prepare dietary recommendations has been established as a core educational component through a Delphi method with patients, caregivers, and clinicians (Ghaddar et al, 2022), and having access to educational resources may increase confidence and reduce associated burden (Rangira et al, 2022). Indeed, caregivers in prior studies have indicated wanting modified food recipes (Howells et al, 2021b), and a recent pilot randomised clinical trial involving 22 stroke patients found that attending a 6-week food preparation program (i.e., performing oral motor exercises, identifying thickeners and food textures, practising meal preparation) was associated with better self-perceived dietary and psychosocial well-being (Lin et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This could assist in overcoming challenges associated with meal preparation and selection, given many carers have reported to resorting to trial-and-error methods (Howells et al, 2021a;Nund et al, 2014aNund et al, , 2014c. Knowing how to select and prepare dietary recommendations has been established as a core educational component through a Delphi method with patients, caregivers, and clinicians (Ghaddar et al, 2022), and having access to educational resources may increase confidence and reduce associated burden (Rangira et al, 2022). Indeed, caregivers in prior studies have indicated wanting modified food recipes (Howells et al, 2021b), and a recent pilot randomised clinical trial involving 22 stroke patients found that attending a 6-week food preparation program (i.e., performing oral motor exercises, identifying thickeners and food textures, practising meal preparation) was associated with better self-perceived dietary and psychosocial well-being (Lin et al, 2021).…”
Section: Discussionmentioning
confidence: 99%